Caracterização morfodinâmica do estuário do Rio Açu, Macau/RN - Rocha, Ana Karolina Rodrigues da (2010)
Estuaries are coastal environments ephemeral life in geological time, derived from the drowning of the shoreline as a function of elevation relative sea level. Such parallel systems is characterized by having two sources of sediment, the river and the sea. The study area comprises the Acu River estuary, located on the northern coast of Rio Grande do Norte State, in a region of intense economic activity, mainly focused on the exploration of oil onshore and offshore, likely to accidental spills. In the oil sector are developed for salt production, shrimp farming, agriculture, fisheries and tourism, which by interacting with sensitive ecosystems, such as estuaries, may alter the natural conditions, thus making it an area susceptible to contamination is essential in understanding the morphodynamic variables that occur in this environment to obtain an environmental license. Information about the submarine relief the estuaries are of great importance for the planning of the activity of environmental monitoring, development and coastal systems, among others, allowing an easy management of risk areas, and assist in the creation of thematic maps of the main aspects of landscape. Morphodynamic studies were performed in this estuary in different seasonal periods in 2009 to observe and quantify morphological changes that have occurred and relate these to the hydrodynamic forcing from the river and its interaction with the tides. Thus, efforts in this area is possible to know the bottom morphology through records of good quality equipment acquired by high resolution geophysical (side-scan sonar and profiler current by doppler effect). The combination of these data enabled the identification of different forms of bed for the winter and summer that were framed in a lower flow regime and later may have been destroyed or modified forms of generating fund scheme than the number according Froude, with different characteristics due mainly to the variation of the depth and type of sedimentary material they are made, and other hydrodynamic parameters. Thus, these features background regions are printed in the channel, sandy banks and muddy plains that border the entire area